2018
DOI: 10.2147/ott.s176252
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CCNO decreases the tumorigenicity of gastric cancer by inducing apoptosis

Abstract: PurposeRecently, Cyclin O (CCNO) has been reported to be a novel protein of the cyclin family. However, the clinical significance and functional roles of CCNO in human cancer, including gastric cancer (GC), remain largely unexplored. In this study, we investigated the clinical and functional roles of CCNO in GC.MethodsWe analyzed CCNO expression patterns in GC patients. To investigate the role of CCNO in malignancy of GC, we used lentivirus-delivered short hairpin RNA to knockdown CCNO expression in GC cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…In the present study, CCNO was identified as the target of miR-302b/c/d-3p. In addition, elevated mRNA expression of CCNO has been reported in GC tissues and depletion of CCNO can significantly induce cancer cell apoptosis both in vitro and in vivo [ 18 ], which is partially consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, CCNO was identified as the target of miR-302b/c/d-3p. In addition, elevated mRNA expression of CCNO has been reported in GC tissues and depletion of CCNO can significantly induce cancer cell apoptosis both in vitro and in vivo [ 18 ], which is partially consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, CCNO was identified as the target of miR-302b/c/d-3p. In addition, elevated mRNA expression of CCNO has been reported in GC tissues and depletion of CCNO can significantly induce cancer cell apoptosis both in vitro and in vivo [18], which is partially consistent with our findings. Our study also revealed that up-regulated RACK1 inhibited CCNO expression by promoting miR-302b/c/d-3p expression, resulting in accelerated apoptosis in CSCC cells, as evidenced by decreased Bcl-2 and Cyclin D1 expression, and increased cleaved PARP and cleaved caspase 3 expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Aberrant expression of key MCC specific genes can also be observed in many cancers and some evidence suggests they may play functional roles [138][139][140]. The aberrant expression or depletion of GEMC1 and MCIDAS in cancer cell lines has been shown to impact DNA replication and could potentially activate transcription factors such as E2F4, p73 and FOXJ1 that have been implicated in cancer development, and could provoke centriole amplification and mitotic defects [26][27][28].…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…The pelvic RT dose was 45 Gy, delivered in 25 fractions, with a simultaneous integrated boost of 120-130% to regional LN metastases. RT response was evaluated by MRI in the fourth week of pelvic EBRT (36)(37)(38)(39)(40)(41)(42)(43)(44)(45) Gy in 20-25 fractions). A weekly cisplatin regimen (30-70 mg/m 2 ) was administered for six cycles to all patients.…”
Section: Patientsmentioning
confidence: 99%